Virtual Reality / Steven M. LaValle, University of Oulu - LaValle, Steven M.
This book covers the fundamentals of virtual reality systems, including geometric modeling, transformations, graphical rendering, optics, the human vision, auditory, and vestibular systems, interface design, human factors, developer recommendations, and technological issues